NATO & CSDP: Can the EU afford to go solo? - Demetriou, Petros (My University, 2016)
This article negotiates whether Common Security and Defence Policy (CSDP) can replace North Atlantic Treaty Organisation's (NATO) military capabilities. It examines the following two cases: (1) Whether European integration can spell the end for NATO and (2) Whether NATO will continue to prevail over the EU's CSDP. To get there the article goes through issues such as the transatlantic gaps and differences, EU's efforts for more autonomy in military actions, and problems that arise within the EU and the US. At the same time it examines the reasons behind NATO's success up until now. The author's conclusion is that the EU at the moment cannot afford to go solo and thus will have to rely on NATO for any future military actions.
Keywords: NATO; CSDP; ESDP; EU; US; Integration; Security